Green zero valent iron nanoparticles dispersion through a sandy column using different injection sequences - Soares, António Alves (2019)
The contamination of soils is a global environmental problem that urges an increased effort to recover polluted sites. In Europe, there are an estimated 20,000 polluted sites that need to be remediated and around 350,000 sites that are classified as potentially contaminated by the European Environment Agency (EEA). Remediation is a part of the solution to this problem, requiring the most innovative and sustainable technologies. In this context, the use of zero valent iron nanoparticles (nZVI) is a promising, low cost and efficient technology for the remediation of soil and groundwater contaminated with a wide range of organic and inorganic pollutants. Among the nZVIs, the ones produced using Green synthesis methods (green nZVIs (gnZVI)) using natural extracts, such as green tea, are increasingly considered an alternative technology for the future. However, there are issues related to the application of gnZVI in soil that are still not fully understood, requiring further research, among these is the study of their transport in soils. Therefore, this work aims to study the transport of gnZVIs in sandy soils under diverse conditions such as soil particle size, soil saturation level and injection sequence. Several experiments were performed in an acrylic column with two sandy soils with different particle sizes (between 0.5 and 1.0 mm and higher than 1.0 mm), using two distinct water saturation conditions (saturated and dry) and four injection sequences. After these tests the distribution of the gnZVI along the soil column was determined by atomic absorption spectroscopy. This work allowed concluding that the injection sequence might be one of the most important factors influencing the rate of nZVI dispersion through a sandy column. According to the results it was possible to propose, for distinct types of contamination (deep, superficial, hot spot or dispersed), the most appropriate injection sequence.